Flexibility in contemporary housing: A comparative analysis of a residential building in Vračar and a housing complex in Velika Remeta - Ristić Trajković, Jelena (Arhitektura i urbanizam, 2024)
This paper presents two examples of recently completed residential buildings in Belgrade and Velika Remeta (Irig Municipality). These buildings exemplify how flexibility is applied in contemporary housing designs in line with users' needs. The urban and architectural composition reflects a design approach considering contextual constraints and form-functional requirements to achieve an optimal housing standard. The implementation of the flexibility concept in the selected examples is considered in the design phase: (1) in the first example, flexibility refers to the use of the entire structure, not just the apartment unit, and (2) in the second example, flexibility is applied in the conceptual phase of the design process through the offer of seven variant types of the same design.
Keywords: housing typologies; quality of housing; flexible housing